Anomalous Left Coronary Artery from the Pulmonary Artery (ALCAPA) Syndrome: Pathophysiology, Clinical Manifestations, and Management Strategies - Donaldo Emiliano Silva López; Sussan Irlanda Méndez Ynostroza; Karla Valdos Rodríguez; Magda Karina López Saldaña; José Antonio Velarde Chávez; Ximena Alejandra Aldama Pimentel (International Journal of Medical Science and Clinical Research Studies, 2024)
Anomalous Left Coronary Artery from the Pulmonary Artery (ALCAPA) syndrome is a rare congenital cardiac anomaly characterized by the abnormal origin of the left coronary artery from the pulmonary artery instead of the aortic root. This anomaly results in compromised myocardial perfusion, particularly under conditions of increased oxygen demand, leading to myocardial ischemia, left ventricular dysfunction, and potentially severe complications such as mitral regurgitation, heart failure, and sudden cardiac death. The pathophysiology of ALCAPA involves a complex interplay of coronary artery steal phenomenon, collateral vessel development, and ventricular remodeling. Early diagnosis is critical, often achieved through echocardiography, cardiac MRI, or coronary angiography, which helps in planning surgical intervention. The mainstay of treatment is surgical correction to re-establish a dual coronary artery system, with techniques including direct reimplantation of the anomalous coronary artery into the aorta or the creation of an intrapulmonary tunnel. This article provides a comprehensive review of the current understanding of ALCAPA syndrome, emphasizing its pathophysiology, clinical presentation, diagnostic modalities, and surgical management, along with outcomes and prognostic factors.